Miracles Revisited New Testament Miracle Stories and their Concepts of Reality. - Alkier, Stefan; Weissenrieder, Annette (Berlin : De Gruyter, 2013)
The book revisits New Testament and other miracle stories with regard to three dimensions: 1. It proposes to connect the interpretation of miracle stories to concepts of reality. 2. It emphasizes the political implications of miracle stories and their interpretations. 3. It demands to read miracle stories within its contexts. The book addresses how ancient concepts of reality, always complex, come to expression in stories of miraculous healings and their reception in medicine, art, literature, theology and philosophy, from classic antiquity to the Middle Ages.
The Rhetoric of Violence and Healing in the Church of Prophites Elias in ThessalonikiThe Wondrous World of the Cinema: Types of Depictions of the Miraculous in Jesus Films; V Rethinking the Miraculous; Miracles Revisited. A Short Theological and Historical Survey; New Testament Healing Narratives and the Category of Numinous Power; The Concept of Miracle and the Concepts of Reality. Some Provisional Remarks; Marvels, Miracles, Signs and the Real: Peirce's Semiotics in Religion and Art; List of Contributors; Index of Subjects and Persons; Index of Biblical Sources; Index of Authors.
Description based on print version record.
Includes bibliographical references and indexes.
Keywords: Bible. New Testament -- Criticism, interpretation, etc; Miracles -- Biblical teaching; Bible. -- Criticism, interpretation, etc; Reality -- Biblical teaching; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Electronic books